Aspectos socioculturais e registro ortográfico de alunos com defasagem idade-série - Subtil, Carla Inês de Camargo (My University, 2014)
The research on orthographic mistakes registered in textsof candidates to the 2005/ 2006 Supplemental Tests/ RS- Brazil, had the objective of subsidize the pedagogic actions that orientate the educational work referring to orthography. Data were collected from texts written by students of both private and state schools. The mistakes were analyzed and classified according to the categories proposed by Bortoni-Ricardo (2005). Also, it was made a study of social and cultural characteristics of two groups of students, possible candidates to Supplemental Tests. It was verified that the high number of orthographic mistakes is due to few reading exercises and few writing activities.
">A pesquisa sobre erros ortográficos registrados na escrita de candidatos aos Exames Supletivos/RS 2005/2006 teve por objetivo subsidiar as ações pedagógicas que norteiam o trabalho docente no que se refere a ortografia. Levantaram-se erros ortográficos de produções escritas de candidatos oriundos da rede pública e particular de ensino. Conforme as categorias de erros sociolingüísticos de Bortoni-Ricardo (2005), analisaram-se e classificaram-se esses erros em quatro categorias. Fez-se também um estudo de características socioculturais de dois grupos com defasagem idade-série, possíveis candidatos a Exames Supletivos, um da rede pública e outro da rede particular. Verificou-se que o elevado número de erros ortográficos se deve ao pouco insumo de leitura e escrita.
Keywords: Linguística; Ortografia; Educação de Jovens e Adultos; Aspectos socioculturais; Análise de erros; Sociolingüística; Orthography; Youths and Adults Education; Cultural and social aspects; Analysis of mistakes